2013
DOI: 10.1002/j.0022-0337.2013.77.12.tb05644.x
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Clinical Learning in an Emerging Dental School: An Investigation in International Collaboration Between Michigan and Ghana

Abstract: The dearth of dental faculty members is a widely known problem that is exacerbated in countries that are attempting to begin dental education programs. This collaboration between Kwame Nkrumah University of Science and Technology and the University of Michigan investigated if dental students who have just started their clinical dental education can learn the knowledge and skills required for identifying and restoring cavitated caries lesions through compact course delivery. There were three instructional block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Not only foreign students but also educators should be invited. A previous study related to international collaboration has suggested that an integrated compact course delivery model may assist in increasing the students’ experience and confidence . In this process, cooperation from international student advisers is essential for inviting foreigners to schools .…”
Section: Discussionmentioning
confidence: 99%
“…Not only foreign students but also educators should be invited. A previous study related to international collaboration has suggested that an integrated compact course delivery model may assist in increasing the students’ experience and confidence . In this process, cooperation from international student advisers is essential for inviting foreigners to schools .…”
Section: Discussionmentioning
confidence: 99%
“…There appears to be an underreporting in the published literature about partnerships in IoDE, indicating limited research of the motivations and outcomes of these partnerships. In the 14 articles with reported partnerships, 4 involved the pairing of a school in the HICs with one or more schools in the LMICs (44,47,58,76).…”
Section: Institutional Partnershipsmentioning
confidence: 99%